All the Mandibular Incisors with Double Canals in a Single Patient: A Rare Case - Daokar, Sadashiv G (J Int Oral Health, 2015)
Single rooted tooth are considered to be the easiest for root canal treatment. The literature has documented cases with single rooted tooth showing more than single canal. Understanding of root canal morphology thus is an important aspect to be considered for successful endodontic treatment. The case presented here shows a rare entity of having double canals in all the mandibular incisors in a single patient.